Optimalisasi Kompetensi Pedagogis Guru dalam Pendampingan Masa Aqil Baligh - Mukminin, Umil; Fakhria, Sheila; Khotimah, Husnul (Institut Agama Islam Negeri Kediri, 2023)
Abstract: Aqil baligh is a thing that indicates the relationship between the maturity of the mind (aqil) with the physical maturity (baligh) of the individual. Currently, there are many phenomena where teenagers who have reached puberty but do not understand the obligations they are responsible for. With the teacher in accompanying students, those who enter puberty can get an understanding of the changes in themselves. The objectives of this study are: (1) Describe the role teachers in mentoring students during puberty in MTsN 8 Kediri, (2) Analyzing supporting and inhibiting factors in mentoring students during puberty in MTsN 8 Kediri. This research uses a type of qualitative research with a descriptive approach. Data collection techniques with observation, in-depth interviews, and documentation. The process of checking data uses triangulation techniques, and source triangulation. Based on the results of this study, it was found: (1) Teachers can optimize their pedagogical competencies in assisting students during puberty, namely; Teachers carry out their role as educators and instructors as guides, as examples, and as facilitators and learning resources for students (2) The supporting factors of student assistance are teacher awareness of the importance of mentoring, cooperation between Fiqh teachers and religious teams, as well as adequate infrastructure and facilities. While the inhibiting factors are limited time for mentoring, as well as the environment and association. Abstrak: Aqil baligh merupakan hal yang menandakan terkaitnya kedewasaan akal (aqil) dengan kedewasaan fisik (baligh) individu. Saat ini banyak fenomena dimana para remaja yang telah baligh tetapi belum paham mengenai kewajiban yang menjadi tanggungjawabnya. Dengan adanya guru dalam mendampingi peserta didik, maka mereka yang memasuki aqil baligh bisa mendapatkan pemahaman tentang perubahan dalam dirinya. Tujuan penelitian ini adalah untuk menganalisis peran guru dalam mendampingi peserta didik masa aqil baligh di MTsN 8 Kediri beserta faktor pendukung dan penghambat dalam proses pendampingan tersebut. penelitian ini menggunakan pendekatan deskriptif kualitatif. Teknik pengumpulan data dengan observasi, wawancara dan dokumentasi. Proses pengecekan data menggunakan triangulasi teknik, dan triangulasi sumber. Hasil penelitian menyebutkan bahwa: (1) guru bisa mengoptimalkan kompetensi paedagogis yang dimilikinya dalam pendampingan peserta didik masa aqil baligh yaitu; guru menjalankan perannya sebagai pendidik dan pengajar, sebagai pembimbing, sebagai teladan, serta sebagai fasilitator dan sumber belajar bagi peserta didik (2) Faktor pendukung dari pendampingan peserta didik yaitu kesadaran guru mengenai pentingnya pendampingan, adanya kerja sama antara guru dan tim keagamaan, serta sarana prasarana dan fasilitas yang memadai. Sedangkan faktor penghambatnya yaitu terbatasnya waktu pendampingan, serta lingkungan dan pergaulan.